Unraveling market access opportunities through one stop border posts: Traders’ perceptions on the influence of administrative practices and cross-cultural competences - Toba Nguvila; Elia John; Ismail Juma Ismail (LBS Journal of Management & Research)
Purpose – In the process of one stop border posts (OSBP), market access is dynamic. In this context, administrative practices and cross-cultural competence among traders are crucial for market access. However, there is limited research on how cross cultural competences can strengthen the influence of administrative practices on market access among small traders. This study therefore aims at exploring this relationship. Design/methodology/approach – This study used structured questionnaire to collect data from 328 traders of maize, onion and tomatoes at Namanga OSBP. Data were analyzed using PLS-SEM. Findings – The results of this study imply that administrative practices and cross-cultural competences significantly and positively influence market access. Finally, cross-cultural competence is a significant positive moderator of the relationship between administrative practices and market access. Originality/value – The results suggest that cross-cultural competence is a significant moderator of the relationship between administrative practices and market access. This adds new knowledge in the literature on how cross-cultural competences of the traders can strengthen the influences of administrative practices at the OSBPs for high market access.